The American Housing Crisis: A Theft, Not a Shortage - Blair Fix (Economics from the Top Down, 2024)
If mainstream economics teaches us one lesson, it's that when something becomes unaffordable, it's because of a shortage. And that brings me to the US housing crisis. In America, housing is getting less affordable. So there must be a short supply, right? Not necessarily. You see, shortage is not the only route to unaffordability. There's also … theft. Here's how it works.
Keywords: P1; R; D3; O15; 330; crisis; distribution; housing; affordability; price; United States